ANTECEDENT REVISIT INTENTION AMUSEMENT PARK - Ayu Laras Wati; Sri Vandayuli Riorini (Business, Economics dan Entrepreneurship, 2023)
The purpose of this research is to analyze the effect of Natural Environment, Service and Amenities, Satisfaction with Destination and Consumer-Based Brand Equity on Revisit Intention. The reopening of tourist destinations that were closed and the opening of new tourist destinations will be a factor in the lack of Revisit Intention intensity in a tourist destination. The management of the Amusement Park must pay attention to what factors can affect the Revisit Intention of their tourist attractions. The sampling technique in this study used "purposive sampling" with the criteria of respondents being individuals who had visited an amusement park at least once. This study uses primary data obtained through questionnaires distributed to 190 respondents. Data were analyzed using the Structural Equation Model method run by the AMOS program. The results showed that there were three hypotheses that had a positive effect and one hypothesis that had no positive effect.